Socio-ecological market economy: A research approach - Pysz, Piotr (1941- ); Jurczuk, Anna E.; Moszyński, Michał (Publishing House of Wroclaw University of Economics and Business, 2023)
The aim of this article was to present the possibilities offered by the ordoliberal theory that predispose it to determine a socio-economic order which makes it possible to tackle the dysfunctions and crises that afflict today’s economy and all human civilisation, especially in the ecological dimension. The analysis is based on critical study of the professional literature on the subject in question, which includes both publications on ordoliberal thought and texts which identify the threats present in the modern world. The ordoliberal theory of economic governance shows the potential for its development to include environmental issues, as well as its application as an intellectual basis for socio-economic policies capable of helping to solve contemporary problems. This article represents one of the first attempts to complement the ordoliberal theory of economic order and the concept of the Social Market Economy with ecological aspects.
Argumenta Oeconomica, 2023, Nr 2 (51), s. 101-112
Keywords: ordoliberalism; social market economy; economic order; ecological economics